2023
DOI: 10.3390/foods12163114
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Sensory Properties of Poppy Sherbet by Turkish Consumers and Changes in Quality Properties during Storage Process

Behiye İncisu Aydoğdu,
Nazan Tokatlı Demirok,
Seydi Yıkmış

Abstract: Poppy is an important edible plant containing bioactive components. This study aimed to produce good-tasting poppy sherbet by determining the content using a response surface methodology (RSM). At the same time, bioactive components, phenolic compounds, and color properties were investigated in optimum poppy sherbet during storage; 0.26 g of dried corn poppy flowers, 0.15 g of citric acid, and 4.29 g of sucrose values were the most promising, achieving high scores for color, smell, taste, and general acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…In this study, gallic acid, which had the highest amount, showed a significant decrease of (29.21 ± 0.41 to 21.12 ± 0.30 μg/mL) p < 0.05 during the storage period. Similarly to this study, in a study where poppy sherbet was evaluated during storage (30 days), as the time increased, protocatechuic acid (1.146 ± 0.048, 1.047 ± 0.038 μg/mL) and gallic acid (23.886 ± 0.164, 23.403 ± 0.343 μg/mL) nonsignificant decreased . The values of the phenolic compounds gallic acid, gentisic acid, vanillic acid, catechin, ferulic acid, neohesperidin, quercetin, coumarin, p -coumaric acid, and hydroxybenzoic acid at the beginning of storage were higher than the values obtained by Aydoğdu et al The reason for this difference is thought to be due to the phenolic components of bee bread added to poppy sherbet.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…In this study, gallic acid, which had the highest amount, showed a significant decrease of (29.21 ± 0.41 to 21.12 ± 0.30 μg/mL) p < 0.05 during the storage period. Similarly to this study, in a study where poppy sherbet was evaluated during storage (30 days), as the time increased, protocatechuic acid (1.146 ± 0.048, 1.047 ± 0.038 μg/mL) and gallic acid (23.886 ± 0.164, 23.403 ± 0.343 μg/mL) nonsignificant decreased . The values of the phenolic compounds gallic acid, gentisic acid, vanillic acid, catechin, ferulic acid, neohesperidin, quercetin, coumarin, p -coumaric acid, and hydroxybenzoic acid at the beginning of storage were higher than the values obtained by Aydoğdu et al The reason for this difference is thought to be due to the phenolic components of bee bread added to poppy sherbet.…”
Section: Resultssupporting
confidence: 63%
“…Similarly, Aydoğdu et al. reported that their TFC values were 16.69 ± 0.40, 15.54 ± 0.37, 13.01 ± 0.30, and 12.28 ± 0.21, respectively . This difference may be due to the different methods of adding bee bread and making the sorbet.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations